Ultrahigh Resolution ISAR Imaging of a Target With Unknown and Complex Motion Using SA-NCS Algorithm - Yuexin Gao; Hanwen Yu; Min Xue; Jianlai Chen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
In this manuscript, a novel inverse synthetic aperture radar (ISAR) imaging method for a large target under ultrahigh resolution condition is proposed. Certain problems in the existing ISAR imaging algorithms for ultrahigh resolution imagery are discussed. The problems caused by Keystone Transform under the condition of large bandwidth and long coherent processing interval are analyzed. Moreover, various means of focusing the signals with polynomial phase are analyzed as well. In order to solve these problems, the sub-aperture nonlinear chirp scaling (NCS) algorithm is presented. This algorithm divides the data in range-frequency/azimuth-time domain into several blocks. In each block, a modified NCS algorithm is applied to estimate the rotation parameters. The modified NCS algorithm takes the residual phase errors arising from NCS processing into consideration. It can achieve a better-focusing quality without bringing about too much additional computation burden. The proposed method is applied to acquired data, whose processing results are much better in comparison with the certain algorithm. These experiments validate the effectiveness of the proposed algorithm.